PERAN GURU PENGGERAK DALAM MEWUJUDKAN PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA DI SMA NEGERI 1 CIBUNGBULANG - Ima Rahmawati; Fitri Lestari; Hana Lestari; Meinar Endang Pundasah (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
This study aims to find out the role of the driving teacher at SMA Negeri 1 Cibungbulang in cultivating the Pancasila character of students through the Pancasila student profile project. The research method used is descriptive qualitative with data collection techniques through literature articles, interviews and documentation. The results obtained from this study show the role of the Mobilizing Teacher at SMA Negeri 1 Cibungbulang in realizing the Pancasila Student Profile which is in the very good category and is able to apply its role properly in every behavior and action in the school environment. This can be seen from learning activities and activities outside of learning with habits that can foster the Pancasila character of students by instilling the values ​​contained in Pancasila and several strategies that are integrated through intra-curricular, co-curricular and extra-curricular formal education activities which are packaged in entrepreneurial day project activities.